The living faith - Douglas, Lloyd C. 1877-1951 (Houghton Mifflin, 1955)
The faith and teaching of Lloyd C. Douglas went back always to the fundamentals that Christ laid down in the Sermon on the Mount. For him they were not the pattern of an abstract ideal but a definite plan for living--a plan within the reach of all men.